2018
DOI: 10.7567/jjap.57.09td02
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond resonant magneto-optical Kerr effect measurement on an ultrathin magnetic film in a soft X-ray free electron laser

Abstract: Time-resolved magneto-optical Kerr effect (MOKE) measurement was demonstrated on a sample of the Au/Fe/Au heterostructure with the Fe layer of 0.35 nm thickness under Fe M-edge resonance condition. An ultrabrilliant free electron laser (FEL) in the soft X-ray range was facilitated for the detection of transient signals of resonant MOKE from the ultrathin Fe film. A variation in the Kerr rotation angle was successfully observed on the femtosecond timescale. This technique enables us to reveal the transient magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…While theoretical simulations are necessary to make an appropriate understanding of the spectral feature, the strong observed signal indicates that the magneto-optical effect under corelevel resonance is likely useful for experimentally probing magnetic states or dynamics. 2,8,10,[24][25][26][27] This study demonstrated the MOKE with core-level resonance in the ferrimagnetic metal alloy Gd 23 Fe 67 Co 10 . The polar MOKE was successfully measured at the photon energies of the absorption edges, the Fe M-and Gd N-edges, by applying an optical configuration of the grazing incident (reflection) angle.…”
mentioning
confidence: 53%
“…While theoretical simulations are necessary to make an appropriate understanding of the spectral feature, the strong observed signal indicates that the magneto-optical effect under corelevel resonance is likely useful for experimentally probing magnetic states or dynamics. 2,8,10,[24][25][26][27] This study demonstrated the MOKE with core-level resonance in the ferrimagnetic metal alloy Gd 23 Fe 67 Co 10 . The polar MOKE was successfully measured at the photon energies of the absorption edges, the Fe M-and Gd N-edges, by applying an optical configuration of the grazing incident (reflection) angle.…”
mentioning
confidence: 53%
“…Therefore, our prediction is fully based on the leading order response in real systems. The ARPES light source typically bears a beam spot size 10-100µm upon the sample [1,5,35,38], which requests one to consider physical phenomena at the optical long-wavelength limit as the experimentally most relevant scenario, in contrast to the otherwise interesting space-resolved nano-ARPES or scanning Kerr magnetooptic microscopy study [39][40][41]. We thus introduce a spatially uniform Gaussian vector potential for the pump pulse vertically shone onto the xy-plane A(t) = A 0 exp(−t 2 /2t 2 0 ) [x cos Ωt + τ ŷ sin Ωt], where τ = 0, ±1 and t 0 the temporary width.…”
Section: Model and Time Evolutionmentioning
confidence: 99%
“…2. TrXMOKE measurements were performed using the pump-probe technique 26 to capture the magnetic moment dynamics with element specificity 27 . FEL pulses were incident at an angle of 45 deg.…”
mentioning
confidence: 99%
“…FEL pulses were incident at an angle of 45 deg. The polarization of incident FEL pulses was linear and the polarization plane of the reflected FEL was analyzed by rotating analyzerellipsometry 26,28 . The polarization analyzer consisted of a multilayer mirror and a micro channel plate (MCP), both of which rotate simultaneously.…”
mentioning
confidence: 99%
See 1 more Smart Citation